UV based process for E.coli and Coliphage in secondary effluent for wastewater reclamation and reuse - Marfiah, Ab. Wahid, Dr.; Ilho, Kim, Dr.; Naoyuki, Yamashita, Dr.; Hiroaki, Tanaka, Prof.; Aminuddin, Mohd. Baki, Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia (IEM), 2013)
Link to publisher's homepage at http://www.myiem.org.my/